Diagnostic value of 68Ga‐DOTATATE PET‐CT imaging for staging of ER+/PR+ HER2‐ breast cancer patients with metastatic disease: Comparison with conventional imaging with bone scan, diagnostic CT and 18F‐FDG PET‐CT in a prospective pilot trial. Issue 6 (21st October 2021) - Nguyen, Andrew; Fullard, Karen; Sheehan‐Dare, Gemma; Tang, Reuben; Chan, Lyn; Ho, Bao; Dear, Rachel; Keane, Joanne; Hickey, Adam; Nandurkar, Rohan; Chen, Julia; Chen, Andrew; et al.
Abstract: Introduction: 18 F‐Fludeoxyglucose PET‐CT (FDG) is increasingly used to stage breast cancer. Most breast cancers express the Oestrogen Receptor (ER) and Progesterone Receptor (PR), and this subtype demonstrates lower activity on FDG imaging. Somatostatin receptors (SSTR) offer a potentially improved radiotracer target for ER + /PR + breast cancer. We present the first in vivo clinical study comparing 68 Ga‐DOTATATE PET‐CT (DOTA) to FDG and conventional imaging (bone scan and diagnostic CT), in metastatic ER + /PR + human epidermal growth factor receptor 2 (HER2) negative breast cancer. Methods: Patients with clinically progressive metastatic ER + /PR + HER2‐ breast cancer underwent restaging with DOTA, FDG and conventional imaging. Scans were analysed visually, and semi‐quantitatively. Wilcoxon‐Rank Scoring was used to assess significance. Results: Ten women (mean age 57 years) underwent imaging. 8/10 demonstrated disease on both DOTA and FDG. 2/10 positive on conventional imaging, but DOTA − /FDG −, and had no disease progression at 1‐year follow‐up. Heterogeneity of uptake was seen between DOTA and FDG with 5 bone lesions DOTA + /FDG − and 1 bone lesion FDG + /DOTA − . Twenty‐one visceral lesions were FDG + /DOTA − (2 patients), with 10/21 identified on conventional imaging. Maximum standard uptake values (SUV max) of DOTA were greater than FDG (10.9 vs. 6.6, P = ns). Four sites were biopsied (3 patients). 3/4 had high ER/PR expression (mean DOTA SUV max 9.4) and 1/4 low ER/PR expression (DOTA SUV max 3.1). Conclusion: Whilst we have not demonstrated DOTA to be superior to FDG in staging of ER + /PR + breast cancers, DOTA may have a role in assessing HR status and treatment decisions; further evaluation of this is warranted.